Study the Behaviour of Hardness properties at different grain size of Libyan Calcium Carbonate-filled HDPE Composite - هناء جمهور; رواد الطاهر الأشهب; ايناس فساطوي; مريم مرغم; امال الفارسي; محمد البوزيدي (Journal of Pure & Applied Sciences, 2023)
In this work, raw Libyan calcium carbonate material, which is available in abundant deposit in Tarhuna city, was employed as a filler for HDPE to improve the qualities of the composite material. Calcium Carbonate rocks were manually broken into small pieces, then ground in a hammer mill to a coarse powder of about 1 mm in size, and then ground to a fine size using a centrifugal mill to increase the surface area. Then, the two volumes were treated with polyethylene glycol (PEG) powder as a binder for the filling material with the polymer, and the extrusion and injection molding technique were used to produce the research samples. The weight percentage of the filling material was (10,20 and 30W%). The diagnostic process for the powders and the composite materials involved thermal gravimetric analysis, infrared analysis, x-rays, and optical microscopy. Results showed that Libyan raw material powder (Calcium Carbonate) can be used as a filler for composite materials due to the strong bonds with polyethylene. Light microscopy showed good distribution and homogeneity in tissue samples prepared. The results of Shore hardness for the composite materials showed that with increasing the degree of softness of the filler material, the hardness increased, reaching from (53 – 54 D) and for the reference sample (49.39- 50 D), as for the coarse size (51.36 -52.6 D).